Analisis Pengaruh Work-Life Balance dan Kompensasi Terhadap Kepuasan Kerja Karyawan Pada Perusahaan Logistik di Surabaya - Aisyah Aurelia; Devina Puspita Sari; Irma Rustini Aju (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2024)
This research was conducted at a Logistic Company in Surabaya, where employee work demands were increasing but inversely proportional to the number of employees who are decreasing due to resignation. High work demands make most employees work overtime, which can affect employees' work-life balance. The company explained that it does not have an overtime system, so employees do not receive incentives as compensation for the extra contributions made. The purpose of this study was to determine the effect of work-life balance and compensation on employee job satisfaction. The study used multiple linear regression analysis. The data used with a sampling technique is saturated sample. The data were processed using SPSS 25 with the results of the t test showing the value of t count 2,519> 2,026 t table and a significance value of 0,016 < 0,05, so that work-life balance partially affects job satisfaction. The t value is 5,104> 2,026 t table and the significance value is 0.000 < 0.05, so compensation partially affects job satisfaction. The results of the f test show the value of f count 18,749 > 4,105 F table and a significance value of 0,000 <0,05, so it can be concluded that work-life balance and compensation simultaneously affect job satisfaction